PENGARUH ILLUSIONS OF CONTROL, OVERCONFIDENCE DAN EMOTION TERHADAP PENGAMBILAN KEPUTUSAN INVESTASI PADA INVESTOR DI YOGYAKARTA - Kartini Kartini; Nuris Firmansyah Nugraha (UII, 2015)
Nowadays Investors often make investment decision irrationally. The decision is often based on their judgment that is far away from rational assumption. When investors face risky situa-tion, there are some objectivities, emotions, and other psychological factors that usually ef-fect their decision making. This purpose of study is to examine the effect of illusions of control, risk tolerance, overconfidence and emotion on investment decision making among investors in yogyakarta. Sample of this study is the investors who are 17 until 40 years old and investing in stocks. This study used purposive, convenience and snow-ball sampling method. There are 86 respondents taken from questionnaire. To test hypotheses, this study employs descriptive analysis and multiple regression analysis. Moreover, by performing multiple regression analysis, this study found that illusions of control does not have a negative significant while overconfidence has a positive significant and emotion has a negative significant influance to the investment decision. Key words: Investment Decision Making, illusions of control, overconfidence and emotion.